PROTOTIPE AUGMENTED REALITY PENGENALAN TATA SURYA BERBASIS ANDROID DENGAN METODE MARKER BASED TRACKING - Wibawa, Agusta Pratama; Pusparini, Nur Nawaningtyas (Infotech: Journal of Technology Information, 2021)
Augmented reality is a device in combining objects between 2D and 3D virtual worlds, there is information that has not been implemented directly to the user, then by providing a respons..Develops using projectors and laptops as information technology, besides the development of mobile (cellular) or android-based information technology that can make it easier for learning, especially the introduction of the solar system, the beginning of the solar system introduced various celestial bodies, both planets and surrounding celestial bodies, in class VI who received the material as a basis before going to the next level, but the teaching and learning process there are several factors that influence i if it is examined that there are elderly teachers who have difficulty keeping up with technological developments, from learning media support tools such as projectors and teaching aids are still very limited, and not all teachers use information technology as a learning medium, the purpose of which is to make an introduction to AR learning media applications android-based solar system for class VI, based on these 3 problems as a solution an educational application is needed that supports learning activities using android augmented reality for the introduction of the solar system with the marker based tracking method, the marker becomes a marker of 3D objects to bring up objects from the virtual world to the real which contains information on each of these objects, in other words visualizing the results of the marker directly into the real world, the final result is the creation of an AR application for learning the introduction of the solar system.